High doses of sodium tungstate can promote mitochondrial dysfunction and oxidative stress in isolated mitochondria. Issue 4 (31st December 2018) - Cheraghi, Ghazale; Hajiabedi, Elnaz; Niaghi, Behnaz; Nazari, Firouzeh; Naserzadeh, Parvaneh; Hosseini, Mir‐Jamal
Abstract: Tungstate (W) is recognized as an agent of environmental pollution and a substitute to depleted uranium. According to some preliminary studies, tungstate toxicity is related to the formation of reactive oxygen species (ROS) under abnormal pathological conditions. The kidneys and liver are the main tungstate accumulation sites and important targets of tungstate toxicity. Since the mitochondrion is the main ROS production site, we evaluated the mechanistic toxicity of tungstate in isolated mitochondria for the first time, following a two‐step ultracentrifugation method. Our findings demonstrated that tungstate‐induced mitochondrial dysfunction is related to the increased formation of ROS, lipid peroxidation, and potential membrane collapse, correlated with the amelioration of adenosine triphosphate and glutathione contents. The present study indicated that mitochondrial dysfunction was associated with disruptive effects on the mitochondrial respiratory chain and opening of mitochondrial permeability transition (MPT) pores, which is correlated with cytochrome c release. Our findings suggest that high concentrations of tungstate (2 mM)‐favored MPT pore opening in the inner membranes of liver and kidney mitochondria of rats. Besides, the results indicated higher tungstate susceptibility in the kidneys, compared with the liver.